An Interplay between Epigenetics and Translation in Oocyte Maturation and Embryo Development: Assisted Reproduction Perspective - Dvoran, Michal; Nemcova, Lucie; Kalous, Jaroslav (Biomedicines, 2022)
Germ cell quality is a key prerequisite for successful fertilization and early embryo development. The quality is determined by the fine regulation of transcriptomic and proteomic profiles, which are prone to alteration by assisted reproduction technology (ART)-introduced in vitro methods. Gaining evidence shows the ART can influence preset epigenetic modifications within cultured oocytes or early embryos and affect their developmental competency. The aim of this review is to describe ART-determined epigenetic changes related to the oogenesis, early embryogenesis, and further in utero development. We confront the latest epigenetic, related epitranscriptomic, and translational regulation findings with the processes of meiotic maturation, fertilization, and early embryogenesis that impact the developmental competency and embryo quality. Post-ART embryo transfer, in utero implantation, and development (placentation, fetal development) are influenced by environmental and lifestyle factors. The review is emphasizing their epigenetic and ART contribution to fetal development. An epigenetic parallel among mouse, porcine, and bovine animal models and human ART is drawn to illustrate possible future mechanisms of infertility management as well as increase the awareness of the underlying mechanisms governing oocyte and embryo developmental complexity under ART conditions.
Keywords: protein translation; epigenetics; oocyte maturation; embryo development